Off-label use of rituximab in patients with systemic lupus erythematosus with extrarenal disease activity: a retrospective study and literature review - Sans-Pola, Carla; Danés, Immaculada; Bosch, Josep Àngel; Marrero-Álvarez, Patricia; Cortés, Josefina; Agustí, Antònia (Frontiers in Medicine, 2023)
Introduction Off-label rituximab is commonly used for patients with systemic lupus erythematosus (SLE) with extrarenal disease activity. Methods The outcomes and tolerability of rituximab in adult patients with non-renal SLE treated at our hospital from 2013 to 2020 were described. Patients were followed-up until December 2021. Data were retrieved from electronic medical records. Response was classified into complete, partial or no response according to the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI 2 K)-based definitions. Results A total of 44 cycles were administered to 33 patients. Median age was 45 years and 97% were female. Median follow-up was 5.9 years (IQR 3.7–7.2). The most frequent symptoms that motivated rituximab use were thrombocytopenia (30.3%), arthritis (30.3%), neurological manifestations (24.2%) and cutaneous lupus (15.2%). After most treatment cycles a partial remission was achieved. The median SLEDAI-2 K score declined from 9 (IQR 5–13) to 1.5 (IQR 0–4) (p < 0.00001). The median number of flares significantly declined after receiving rituximab. Platelet counts significantly improved in patients with thrombocytopenia and patients with skin disorders or neurological manifestations also had a partial or complete response. Only 50% of patients with a predominant joint involvement had either a complete or a partial response. The median time to relapse after the first cycle was 1.6 years (95% CI, 0.6–3.1). Anti-dsDNA levels decreased significantly after rituximab from a median of 64.3 (IQR 12–373.9) to 32.7 (IQR 10–173), p = 0.00338. The most frequent adverse events were infusion-related reactions (18.2%) and infections (57.6%). All patients needed further treatment to maintain remission or to treat new flares. Conclusion A partial or complete response was documented after most rituximab cycles in patients with non-renal SLE. Patients with thrombocytopenia, neurolupus, and cutaneous lupus had better response than those with a predominant joint involvement.